Health information inequalities and child healthcare: Evidence from Indonesia National Socio-Economic Survey 2013 - Sujarwoto, Sujarwoto (JPAS (Journal of Public Administration Studies), 2018)
This study for the first time examines the relationship between health information inequalities and child healthcare access in Indonesia, a developing country has been cited as one biggest emerging Internet users in the world. Data come from the Indonesian National Socio-Economic Survey (Susenas) 2013, which comprises 1.25 million individuals, 250 thousands households, and 497 districts. The results of descriptive and instrumental variable analysis indicate trend of widening disparities across socio-economic status and geographical areas in Internet and child immunisation access. A strong evidence for the causal flow running from a mother’s access to Internet to child immunisation is found. All instruments are highly correlated with mother’s access to Internet but uncorrelated with child immunisation. Supply factors across districts – particularly village health posts (posyandu) – are associated with child immunisation. The results are robust against individual, household and district socio-economic characteristics associated with child immunisation access. The results suggest that increasing mother’s access to Internet may bridge child immunisation disparities in Indonesia.